The kings of Clonmel - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2010)
Halt, Will, and Horace set out for Hibernia, where a quasi-religious group, the Outsiders, is sowing confusion and sedition, and they find that secrets from Halt's past may hold the key to restoring order before the last kingdom is undermined.